EFEKTIVITAS PEMBELAJARAN METODOLOGI PENELITIAN DENGAN PEMAHAMAN MAHASISWA DALAM PENULISAN SKRIPSI - Fahrina Yustiasari Liriwati (CV. Aksara Global, 2023)
This study aims to analyze the effectiveness of research methodology learning with students' understanding in thesis writing. Research methodology plays an important role in equipping students with the knowledge and skills necessary to design, conduct and analyze research effectively. However, challenges in understanding the concepts of research methodology can affect students' ability to write quality thesis. Therefore, this study identified the challenges faced by students in learning research methodology and presented solutions that could be applied to increase learning effectiveness. The research method used was literature study and descriptive analysis. Data was collected through a literature review which included research articles, textbooks and other related sources of information. Data analysis was carried out by identifying common challenges in learning research methodology and recommendations that can be implemented to overcome these challenges. The results of the study indicate that a good understanding of research methodology has a positive impact on student thesis writing. Students who have a good understanding of research methodology tend to plan their research well, collect valid data, carry out appropriate data analysis, use relevant reference sources, and construct strong arguments in their thesis. However, there are challenges such as material complexity, limited resources, lack of practical experience, time constraints, and low motivation that need to be overcome. Recommendations to improve research methodology learning include developing a good curriculum, training lecturers, providing adequate resources and facilities, use of technology in learning, intensive individual guidance, and further research on the effectiveness of research methodology learning. By implementing these recommendations, students are expected to gain a better understanding of research methodology and apply it well in their thesis writing. This increased understanding will have an impact on the quality of thesis writing, a more significant contribution in the field of study, and better preparation for future academic or professional careers.